Community structure of arboreal and soil-dwelling arthropods in three different rice planting indexes in freshwater swamps of South Sumatra, Indonesia - Tili Karenina; Siti Herlinda; Chandra Irsan; Yulia Pujiastuti; Hasbi Hasbi; Suparman Suparman; Benyamin Lakitan; Harman Hamidson; Abu Umayah (Society for Indonesian Biodiversity, 2020)
Abstract. Karenina T, Herlinda S,  Irsan C, Pujiastuti Y, Hasbi, Suparman, Lakitan B, Hamidson H, Umayah A. 2020. Community structure of arboreal and soil-dwelling arthropods in three different rice planting indexes in freshwater swamps of South Sumatra, Indonesia. Biodiversitas 21: 4839-4849.  Differences in the index of rice planting can cause differences in the structure of the arthropod community. This study aimed to characterize the community structure of the arboreal and soil-dwelling arthropods in the three different rice planting indexes (PI) in the freshwater swamps of South Sumatra.  Sampling of the arthropods using D-vac and pitfall traps was conducted in the three different rice planting, namely one (PI-100), two (PI-200), and three (PI-300) planting indexes of the rice. The results of the study showed that the dominant predatory arthropod species in the rice fields were Pardosa pseudoannulata, Tetragnatha javana, Tetragnatha virescens, Pheropsophus occipitalis, Paederus fuscipes, and the dominant herbivorous insects were Leptocorisa acuta, Nilavarpata lugens, and Sogatella furcifera. The abundance of arboreal predatory arthropods was the highest in the PI-300 rice and the lowest in the PI-100 rice.    The abundance of soil-dwelling arthropods was the highest in the rice PI-100, and low in the rice PI-200 and PI-300, but the rice PI-100 had the highest abundance of the herbivorous insects. The rice PI-300 was the most ideal habitats to maintain the abundance and the species diversity of the arboreal predatory arthropods. Thus, the rice cultivation throughout the year was profitable in conserving and maintaining the abundance and species diversity of the predatory arthropods.